Ecology of the researcher. Trends and perspectives - Romero Huamaní, Ruth Mirihan (2018)
In the present article we develop the ecology of the researcher within the framework of the trends of the new University Law 30220, regulations that state the quality of the university and the researcher subject, and its implication with its environment to develop scientific research. Every university professional has a scientific production role; however, this is often not possible to achieve due to a series of factors or phenomena that prevent the development of the scientific professional. The ecology of the researcher consists of the possibilities and virtues that he presents when he relates to human beings and their environment, this is manifested in the welfare state of the research subject in the academic world and his public and private life. The purpose is to analyze and describe the ecological aspects of the researcher to determine their scientific and philosophical profile. The methodology used is descriptive and explanatory because it analyzes the arguments extracted from the bibliographic sources to understand the variables and the survey to measure the opinions on the labor aspect and others of the researcher.